RE/POSICIÓN? DE "TRES MARÍAS Y UNA ROSA": TRES DÉCADAS PARA A/BORDAR LA RESISTENCIA. - Zaliasnik, Yael (Revista Chilena de Literatura, 2010)
The present work explores the conditions and repercussions of staging anew an emblematic play of the dictatorship era in Chile: "Tres Marías y una Rosa," three decades after that period, and without significant modifications. In the words of Raymond Williams, what's the residual, the dominant, the emergent? What is won/lost in this re-staging? How is it perceived ("read")? Are there still residual social images from the dictatorship? What did the play represent 30 years ago, and has that changed today? Inevitably, these questions lead us to the issue of the Chilean textile craft of the "arpilleras" and the women artisans who made these ("arpilleristas"), to our understanding, central to the play, but avoided and forgotten as a resistance movement, as it is not treated in depth in its current staging.